2019
DOI: 10.1038/s41598-019-40737-w
|View full text |Cite
|
Sign up to set email alerts
|

A study of the relationship between the level of anxiety declared by MRI patients in the STAI questionnaire and their respiratory rate acquired by a fibre-optic sensor system

Abstract: Magnetic resonance imaging (MRI) patients often experience anxiety-related respiratory disorders, including hyperventilation, but their respiratory indicators are not routinely monitored during scanning. Free from metal parts and immune to electromagnetic radiation, fibre-optic sensors have the potential to better control the patient’s condition by providing continuous non-invasive monitoring of the respiratory rate (RR). The study was purposed to assess the relationship between anxiety in MRI patients and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 34 publications
(32 reference statements)
1
27
0
Order By: Relevance
“…Technological advances in micro-accelerometers and gyroscopes sensors have facilitated the development of high-performing portable devices which are user-friendly, thus enabling their deployment in multiple settings from space laboratories (Migeotte et al 2016) to the clinical setting. Other techniques are also in development such as, for instance, fiber-optic sensors system by measuring changes in the respiratory rate pattern of patients undergoing MRI examination, to evaluate the degree of anxiety (Dziuda et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Technological advances in micro-accelerometers and gyroscopes sensors have facilitated the development of high-performing portable devices which are user-friendly, thus enabling their deployment in multiple settings from space laboratories (Migeotte et al 2016) to the clinical setting. Other techniques are also in development such as, for instance, fiber-optic sensors system by measuring changes in the respiratory rate pattern of patients undergoing MRI examination, to evaluate the degree of anxiety (Dziuda et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the MMF section, the radial field profile of ( ) , r z ψ along the propagation distance z can be expressed as [11] ( ) ( )…”
Section: Principles and Experimental Setupmentioning
confidence: 99%
“…A complete one heartbeat recorded by an electrocardiograph (ECG) can be represented by a P-wave, QRS-complex, and T-wave or shortened by a PQRST-wave. Dziuda et al reported that the relationship between the anxiety in MRI patients and their RR from the two PQRST-waves acquired by a fibre-optic sensor system [11]. The system presented that non-invasive RR monitoring allows the MRI operator to better control the patient's condition.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the functions of fiber optic technology could reach any part of the curved human body via a textile-based wearable modality such as tights [10,11]. Moreover, compared with electronic devices, optical fiber sensors have various advantages: they are durable, immune to electromagnetic interference, exhibit resistance to salt solutions (i.e., sweat), and possess good biocompatibility with the human body [10][11][12][13]. These unique features make optical fiber sensors particularly suitable for special environments, i.e., MRI environments and the skin surface [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, compared with electronic devices, optical fiber sensors have various advantages: they are durable, immune to electromagnetic interference, exhibit resistance to salt solutions (i.e., sweat), and possess good biocompatibility with the human body [10][11][12][13]. These unique features make optical fiber sensors particularly suitable for special environments, i.e., MRI environments and the skin surface [12]. Among numerous fiber optic sensors, fiber Bragg grating (FBG) sensors are being developed to become a prominent technology and are commercialized in a broad field of applications.…”
Section: Introductionmentioning
confidence: 99%